Social media vlogs and e-wom on man-made tourism destination: Insights from Indonesia - Nofrizal, Nofrizal; N, Arizal (Journal of Business & Banking, 2023)
The use of social media Vlogs and WOM has not been thoroughly researched to stimu-late the intention to visit tourist destinations, especially man-made destinations. Howev-er, social media is currently an effective promotion and branding tool. The purpose of this study is to test whether e-WOM and social media vlogs have an impact on interest in visiting tourist destinations, whether social media vlogs have an impact on e-WOM, and whether e-WOM can be a moderating variable. The object of research is tourists who have visited man-made destinations in Indonesia, with a total of 414 respondents. Data collection is done through an online survey using Google Forms. Structural Equation Modeling (SEM) was used to analyze all hypotheses using SmartPLS 4.0 statistical software. The findings showed that social media vlogs and eWOM effectively drive in-tention to visit artificial tourism destinations, with eWOM positively moderating the relationship between social media vlogs and intention to visit. These results make a sig-nificant contribution to tourism theory and practice in formulating the most appropriate marketing promotion strategy for man-made tourism destinations today.